Repeat courses of SRS in patients initially treated with SRS alone for brain-metastatic melanoma. (June 2016) - Bates, James E; Youn, Paul; Usuki, Kenneth Y; Dhakal, Sughosh; Milano, Michael T
Aim: Stereotactic radiosurgery (SRS) is often used in the treatment of brain metastatic melanoma. Little data exist regarding outcomes of repeat course of SRS in this population. We aimed to identify treatment outcomes and toxicities in melanoma patients treated with repeat SRS after upfront SRS.Patients & methods: We reviewed ten consecutive patients treated with repeat SRS following upfront SRS alone for brain metastatic melanoma.Results: The median overall survival from initial treatment was 17.5 months. The median overall survival from repeat SRS was 6.7 months with a 6-month local control rate of 80%. The majority of patients progressed systemically before death. Four patients reported six adverse events, all grade 1.Conclusion: Prospective study regarding the safety and efficacy of repeat courses of SRS in patients with brain-metastatic melanoma, especially in combination with novel immunotherapies, is warranted.